An Analytical Approach for Nonlinear Buckling Analysis of Torsionally Loaded Sandwich Carbon Nanotube Reinforced Cylindrical Shells with Auxetic Core (Advances in Applied Mathematics and Mechanics, 2022)
The main aim of this paper is to present an analytical approach on the postbuckling for torsionally loaded sandwich carbon nanotube (CNT) reinforced cylindrical shells with the auxetic core. The considered shells consist of three layers, externaland internal CNT reinforced layers, and the auxetic lattice core made by isotropic material. The homogenization model for honeycomb auxetic lattice core is utilized, andthe equilibrium equations are formulated based on the nonlinear Donnell's thin shelltheory with von Kármán geometrical nonlinearities. The three terms of deflection are considered, the Airy's stress function and Galerkin's method are utilized, the explicitexpression of critical buckling of torsionally loaded shells and load-deflection expression of postbuckling states are achieved. The effects of two carbon nanotube reinforcedlayers, the auxetic core layer, the volume fraction of carbon nanotube on the torsionalbuckling behavior are examined and remarked.